DNMT3A-mediated high expression of circ_0057504 promotes benzo[a]pyrene-induced DNA damage via the NONO-SFPQ complex in human bronchial epithelial cells. (December 2022) - Qiu, Miaoyun; Zhang, Nan; Yao, Shuwei; Zhou, Hanyu; Chen, Xintong; Jia, Yangyang; Zhang, Han; Li, Xin; Jiang, Yiguo
Highlights: B[ a ]P induces DNA damage response (DDR) in bronchial epithelial cells. B[ a ]P upregulates circ_0057504 through suppressing DNMT3A-mediated DNA methylation. Circ_0057504 promotes B[ a ]P-induced DDR via modulating NONO-SFPQ complex formation. Abstract: Benzo[ a ]pyrene (B[ a ]P) is a class I carcinogen and hazardous environmental pollutant with genetic toxicity. Understanding the molecular mechanisms underlying genetic deterioration and epigenetic alterations induced by environmental contaminants may contribute to the early detection and prevention of cancer. However, the role and regulatory mechanisms of circular RNAs (circRNAs) in the B[ a ]P-induced DNA damage response (DDR) have not been elucidated. In this study, human bronchial epithelial cell lines (16HBE and BEAS-2B) were exposed to various concentrations of B[ a ]P, and BALB/c mice were treated with B[ a ]P intranasally. B[ a ]P exposure was found to induce DNA damage and upregulate circular RNA hsa_circ_0057504 (circ_0057504) expression in vitro and in vivo. In addition, B[ a ]P upregulated TMEM194B mRNA and circ_0057504 expression through inhibition of DNA methyltransferase 3 alpha (DNMT3A) expression in vitro. Modulation (overexpression or knockdown) of circ_0057504 expression levels using a lentiviral system in human bronchial epithelial cells revealed that circ_0057504 promoted B[ a ]P-induced DNA damage. RNA pull-down and western blot assays showed that circ_0057504 interacted with non-POU domain-containing octamer-binding (NONO) and splicing factor proline and glutamine rich (SFPQ) proteins and regulated formation of the NONO-SFPQ protein complex. Thus, our findings indicate that circ_0057504 acts as a novel regulator of DNA damage in human bronchial epithelial cells exposed to B[ a ]P. The current study reveals novel insights into the role of circRNAs in the regulation of genetic damage, and describes the effect and regulatory mechanisms of circ_0057504 on B[ a ]P genotoxicity.